1998
DOI: 10.1016/s0300-483x(98)00104-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of N-acetylcysteine and 2,3-dimercaptosuccinic acid on lead induced oxidative stress in rat lenses

Abstract: Lead (Pb) is known to disrupt the pro-oxidant/anti-oxidant balance of tissues which leads to biochemical and physiological dysfunction. The present study investigated the effects of exposure on the redox status of the lenses of Fisher 344 rats and examined whether antioxidant or chelator administration reversed these changes. Animals were given 5 weeks of 2000 ppm Pb exposure followed by 1 week of either antioxidant, chelator or distilled water administration. Glutathione (GSH) and cysteine (CYS) levels decrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
24
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 28 publications
4
24
0
Order By: Relevance
“…10 NAC also protects cells against metal-induced oxidative stress injuries. 26,27 In fact, GIC may release free metal ions, such as aluminum or cuprum, at toxic or subtoxic concentrations, as shown previously. 7 A recent study 28 confirms the hypothesis by showing that aluminum induces oxidative stress on glioma and neuroblastoma cell lines.…”
Section: Discussionmentioning
confidence: 60%
“…10 NAC also protects cells against metal-induced oxidative stress injuries. 26,27 In fact, GIC may release free metal ions, such as aluminum or cuprum, at toxic or subtoxic concentrations, as shown previously. 7 A recent study 28 confirms the hypothesis by showing that aluminum induces oxidative stress on glioma and neuroblastoma cell lines.…”
Section: Discussionmentioning
confidence: 60%
“…These levels were similar in the lead and kefir, kefir and control groups. The decrease in GSH level might be due to either the decrease in cystein present (Patra et al, 2001) o r the inhibition of GSH synthesis through the binding of lead to the active component of the enzyme (Neal et al, 1998). It might also be because of the fact that it is used in the removal of free radicals produced after the lead accumulation in blood and tissues (Tandon et al, 2002).…”
Section: Resultsmentioning
confidence: 99%
“…14) Oxidative stress is one of the important mechanisms of the toxic effects of lead. [15][16][17] Several studies reported alternations in antioxidant enzyme activities such as superoxide dismutase (SOD) and glutathione peroxidase (GPx), and changes in the concentrations of some antioxidant molecules such as glutathione (GSH) in lead-exposed animals. 18,19) SOD activity is an important component of the cellular antioxidant system that protects cells from the harmful effects of O 2 − and its derivatives.…”
Section: Introductionmentioning
confidence: 99%